Processing of Inasua as Local Wisdom from Teon, Nila and Serua Communities in Ceram Island - Mahulette, Ferymon; Kurnia, Tri Santi; Serpara, Ridolf; Rupilu, Marselina Ribka (Universitas Negeri Semarang, 2022)
Inasua is a traditionally fermented fish product which is local wisdom of Teon, Nila and Serua (TNS) Communities, Central Moluccas. Inasua processing initially using porkfish (Ruvettus tydemani Weber) as raw material. This fish is rarely found, so the people process inasua using a variety of reef fish. The processing of inasua has been done by the ancestors of the community for a long time, but information about processing this product is very limited. This research aimed to describe the techniques of inasua processing in Waipia, Ceram Island. This research was descriptive qualitative. Data was collected from direct observations in three villages representing three groups of TNS Communities, i.e. Layeni Village (Teonese), Kuralele Village (Nilanese), and Waru Village (Seruans). The processing of inasua was diverse in the three groups of TNS Communities. The people of Teonese usually process of inasua using only salt and salt added coconut sap, while the people of Nilanese using salt only. The people of Seruans usually process inasua using salt only, but some people also added coconut vinegar. This research was expected to conserve of inasua processing culture to support the tourism in Central Moluccas Regency.